Integration of transcriptomics and metabolomics provides metabolic and functional insights into reduced insulin secretion in MIN6 β‐cells exposed to deficient and excessive arginine. Issue 3 (24th February 2022) - Xu, Lianbin; Lin, Xueyan; Li, Xiuli; Hu, Zhiyong; Hou, Qiuling; Wang, Yun; Wang, Zhonghua
Abstract: Previous work demonstrated that arginine is one of the strongest insulin secretagogues. However, knowledge of the mechanisms linking chronic arginine metabolism with β‐cell function and insulin secretion is relatively limited. After preliminary selection of concentration according to the cell proliferation, the MIN6 pancreatic β‐cells were randomly assigned to culture in 0.04 mM (low‐arginine, LA), 0.4 mM (standard‐arginine, SA), or 8 mM arginine (high‐arginine, HA) for 24 h. Following the treatment, a combination of transcriptomics and metabolomics, together with a series of molecular biological tests were performed to investigate the responses of β‐cells to varied arginine availability. Our results showed that HA treatment reduced the chronic insulin releases, and LA and HA treatments decreased the glucose‐stimulated insulin secretions (GSIS) of β‐cells relative to the SA group ( p  < .05). Transcriptomics analysis indicated that LA administration significantly inhibited oxidative phosphorylation and ATP metabolic process but promoted DNA repair and mRNA processing in β‐cells, while HA administration affected ammonium ion metabolic process and mRNA export ( p  < .05). Both LA and HA regulated the expressions of genes involved in DNA replication, cell‐cycle phase transition, and response to oxidative stress ( p  < .05). Protein‐protein interaction and transcription factor analyses suggested that Trp53 and Nr4a2  genes may play key roles during arginine stimulation. On the contrary, metabolomics analysis demonstrated that the differentially expressed metabolites (DEM) of MIN6 β‐cells induced by LA were mainly enriched in glycerophospholipid metabolism, linoleic acid metabolism, and purine metabolism, while most DEMs between LA vs. SA comparison belonged to amino acid metabolism. When combined the three groups, co‐expression analysis suggested that insulin secretions had strong associations with L‐pyroglutamic acid, L‐glutamate, and creatine concentrations, while intracellular insulin contents were mainly correlated to L‐arginine, argininosuccinic acid, and phosphorylcholine. At last, integrated analysis of transcriptomics and metabolomics showed that glycerophospholipid metabolism, biosynthesis of unsaturated fatty acids, and amino acid metabolism were the most relevant pathways in β‐cells exposed to abnormal arginine supply. This descriptive bioinformatics analysis suggested that the disturbed carbohydrate, lipid, and amino acid metabolisms, as well as the increased apoptosis and elevated oxidative stress, contributed to the reduced insulin secretion and lower GSIS in β‐cells induced by LA or HA treatments, while some underlying mechanisms need to be further explored.